PHYSICAL THERAPY AND OCCUPATIONAL THERAPY FOR MILITARY PERSONNEL AFTER BLAST-RELATED THORACIC TRAUMA - Nagorna, O. B.; Kunynets, O. B.; Kravets, K. P. (Rehabilitation and Recreation, 2025)
Chest injury in military personnel is one of the most common combat injuries among military personnel. This is the result of explosive waves, falls, contusion or compression with heavy objects withoutpenetration into the chest cavity. The most typical clinical manifestations include the contusion of the chest wall, fractures of the ribs, lung damage, ventilation disorders and respiratory failure. These conditions canlead to a decrease in physical activity, impaired respiratory function and reduce the quality of life in the affected persons. The aim is to analyze current scientific evidence and clinical guidelines regarding physical therapy for military personnel after blast-related thoracic trauma. Materials and methods. Storing,analysis and systematization of scientific literature published between 2019 and 2024 based on search inPubMed, Scopus and Web of Science Databases. Results. Clinical recommendations, protocols, systematic examinations and results of original physical therapy studies after a blast-related thoracic trauma of chest in military personnel illuminate the need to supplement traditional methods of physical therapy such as early mobilization, breathing gymnastics, posture drainage daily activities. Individualized physical therapyprograms are developed and implemented to address the specific needs of patients during the pre-operative,in-hospital, and post-hospital periods, focusing on the prevention of long-term complications. This systematic approach effectively contributes to the restoration of respiratory function, improved physical capacity,and reduced risk of complications.Conclusions. Physical therapy – including breathing exercises, positional treatment, occupational therapy and motor rehabilitation – is a key component in the recovery process after breastfeeding. Despite itsprevalence, the rehabilitation management of the military after breast trauma remains a lot of investigated,especially in the context of constant military conflict.